Content Analysis of Promotional Messages Conveyed by Retailers in Mannar District - Mary Theresa, S.; Shivany, S. (Research gate, 2018)
Since the beginning of conflict resolution in Sri Lanka, Retailers in Mannar have been promoting their products to consumers via different media vehicles. Over the years, the promotional processes and systems used by retailing have been tailored and modified in order to meet the demands of the consumers. Nowadays promotional messages are greatest important to all business to realize the objectives of the businesses successfully. Suitable promotional messages support consumers for their purchase decisions. Promotional message content is important, because those fascinate consumers. Today’s retailers must find new ways to attract consumers and inspire high levels of customer retention. Purpose of this research is to identify the different contents of promotional messages conveyed by the retailers in Mannar, where many retailers penetrated after conflict resolution. This research analyzed the contents of promotional messages in 24 Newspaper Advertisements and 26 Catalogs. This research frequently identified the contents of pesticides and herbicides promotional messages. Based on Carlson’s classification contents are summarized based on product oriented, process oriented, Image oriented, environmental reality orientated and integrated promotional messages. Content analysis was used to classify those promotional messages into five categories. Different promotional messages are identified from the different product advertisements. There is inadequate promotional messages on environmental reality, and integrated messages identified in this study. Consumers seek for innovation, creativity as well as the environmental friendly concern. Therefore, present study provides implications to retail sector in Mannar to design further promotional messages which integrate the orientations on product, process, Image, and Environmental reality.
Keywords: Advertisements; Content Analysis; Catalogues; Promotional Messages; Retailers